Perancangan Sistem Pengendalian Suhu Air Pada Shower Therapy Dengan Fuzzy Logic - Eko Arianto (Jurnal Teknologi, 2022)
Therapy is a form of health service to develop, maintain, and restore body movement and function by using manual handling and equipment. One of the therapies that many people need is for relaxation and reducing fatigue. One alternative is to use water as a medium (hydrotherapy). The pressure and temperature of the water used for shower therapy has been shown to provide physiological changes in humans. Shower therapy with warm water is strongly influenced by room temperature. The difference in outdoor air temperature (room) with the temperature of the water for bathing is very large will cause serious physiological problems. Therefore, to prevent the risk of differences in room temperature and water temperature being too large when bathing and/or shower therapy, a water temperature control system is needed that can maintain the temperature difference at a certain level. With a fuzzy logic controller system, the water temperature will be able to be controlled to adjust the outdoor air temperature (room). By adjusting the value of delta (∆) outside air temperature and water temperature, extreme temperature differences can be handled. The prototype of the water temperature control system in shower therapy with fuzzy logic has been successfully created with minimal functions with a water mixer system using solenoid valves. The water mixer can work at a minimum with the water temperature output which is still unstable and less accurate with a fairly high deviation. Setting the value of ΔT >5 produces a more stable water temperature output with an average deviation of <10%. The effect of pressure and water flow has not been seen and has not been observed.